Collaborative conversations during the time of COVID‐19: Building a "meta"‐learning community. Issue 1 (6th July 2021) - Ferguson, Lisa; Rentes, Victor C.; McCarthy, Lauren; Vinson, Alexandra H.
Abstract: Problem: COVID‐19 created new research, clinical, educational, and personal challenges, while simultaneously separating work teams who were under work‐from‐home restrictions. Addressing these challenges required new forms of collaborative groups. Approach: To support the department community and the rapid sharing of new research, educational, clinical, and personal efforts, a Core Team from the Department of Learning Health Sciences at the University of Michigan developed a meeting series called the COVID Conversations. This Experience Report shares the organizational structure of the COVID Conversations, proposes a comparison to traditional Learning Communities, and reports the results of a questionnaire that gathered details about department members' COVID‐related activities. Outcomes: We identify and describe salient similarities and differences between the COVID Conversations and the characteristics of Learning Communities. We also developed and piloted a taxonomy for characterizing LHS research projects that may be further developed for use in Learning Community planning, in conjunction with other maturity grids and ontologies. We propose the term "Meta‐Learning Community" to describe the structure and function of the COVID Conversations. Next Steps: In academic medicine, remote work, telemedicine, and virtual learning may be here to stay. The COVID Conversations constitute a distinct and innovative form of collaborative work in which separate teams addressing distinct goals, yet sharing a common passion to tackle the issues brought by the pandemic, are able to share experiences and learn from one other. The challenges of COVID‐19 have made evident the need for multiple forms of organizing teamwork, and our study contributes the notion of a "Meta"‐Learning Community as a new form of collaborative work.